I wish you more - Rosenthal, Amy Krouse; Lichtenheld, Tom (San Francisco : Chronicle Books, 2015)
In simple text and pictures, the author and illustrator create a compendium of small daily moments.
Some books are about a single wish. Some books are about three wishes. The infallible team of Amy Krouse Rosenthal and Tom Lichtenheld have combined their extraordinary talents to create this exuberant book of endless good wishes. Wishes for curiosity and wonder, for friendship and strength, laughter and peace. Whether celebrating life's joyous milestones, sharing words of encouragement, or observing the wonder of everyday moments, this sweet and uplifting book is perfect for wishers of every age.--Publisher website.
105298
Keywords: Wishes -- Juvenile fiction; English language -- Comparison -- Fiction; Fiction; Juvenile works; Children's stories -- Pictorial works; Picture books